Application Of Mind Mapping-Assisted Poster Commen Method To Improve Students’ Creative Thinking Skills In Primary School - Mellya Silsiani Dewi; Fauziddin Moh.; Ananda Rizki; Aprinawati Iis; Mufarizuddin Mufarizuddin (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
This research was motivated by the low creative thinking ability of grade IV students of State Elementary School 007, Bangkinang City.. One solution to this problem is using the Mind Mapping-Assisted Poster Commen Method. This study aims to improve the creative thinking skills of grade IV students of State Elementary School 007, Bangkinang City, a total of 23 students, with 12 male and 11 female students. This research method is a class action research carried out in two cycles. Each cycle consists of two meetings and four stages of learning: planning, implementation, observation, and reflection. The research will be conducted in September 2023, using data collection techniques in the form of documentation and observation. At the same time, data analysis techniques include qualitative and quantitative analysis. These research instruments are teacher activity observation sheets, student activity observation sheets, and student worksheets. Based on the results of data analysis, the results of creative thinking skills of grade IV students of State Elementary School 007, Bangkinang City. They were obtained in pre-action with a percentage of learning completeness of 30.43%. In the first cycle of meetings, I had a percentage of learning completeness of 43.47%. Students who completed only 10 students and cycle I meeting II, the percentage of learning completeness increased to 60.86%, with only 14 students completing.  In the second cycle of meetings, I also increased the percentage of learning completeness to 78.26%, with 18 students completing cycle II meeting II, and the percentage of learning completeness increased again to 91.30%, with 21 students completing cycle II meeting II. Thus, it can be concluded that applying the Mind Mapping-Assisted Poster Commen Method can improve the creative thinking ability of grade IV students of State Elementary School 007, Bangkinang City.